2015
DOI: 10.1515/jpm-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical chorioamnionitis at term II: the intra-amniotic inflammatory response

Abstract: Objective Recent studies indicate that clinical chorioamnionitis is a heterogeneous condition and only approximately one-half of the patients have bacteria in the amniotic cavity, which is often associated with intra-amniotic inflammation. The objective of this study is to characterize the nature of the inflammatory response within the amniotic cavity in patients with clinical chorioamnionitis at term according to the presence or absence of 1) bacteria in the amniotic cavity and 2) intra-amniotic inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 179 publications
4
82
0
4
Order By: Relevance
“…Several studies have investigated the diagnostic value of amniotic fluid and maternal serum biomarkers for the detection of chorioamnionitis in pregnant women undergoing amniocentesis. Elevated inflammatory markers such as interleukin 6 (IL-6), IL-8, matrix metalloproteinase 8 (MMP-8), MMP-9, and monocyte chemotactic proteins within amniotic fluid are positive predictors of intra-amniotic inflammation and/or clinical chorioamnionitis (15)(16)(17)(18)(19)(20)(21); however, these markers may have poor positive predictive values for the detection of subclinical, histologic chorioamnionitis and may be variably expressed within the amniotic fluid and fetal membranes during chorioamnionitis (22)(23)(24). Recently, Liu et al (25) reported that surface-enhanced laser desorption ionization-time of flight mass spectrometry (SELDI-TOF-MS) for the detection of human neutrophil defensin 1 (HNP-1) and HNP-2 and calgranulins A and C within amniotic fluid was highly accurate for the diagnosis of subclinical chorioamnionitis, but further studies with larger patient cohorts are required to validate these findings.…”
Section: Diagnosis Of Chorioamnionitismentioning
confidence: 99%
“…Several studies have investigated the diagnostic value of amniotic fluid and maternal serum biomarkers for the detection of chorioamnionitis in pregnant women undergoing amniocentesis. Elevated inflammatory markers such as interleukin 6 (IL-6), IL-8, matrix metalloproteinase 8 (MMP-8), MMP-9, and monocyte chemotactic proteins within amniotic fluid are positive predictors of intra-amniotic inflammation and/or clinical chorioamnionitis (15)(16)(17)(18)(19)(20)(21); however, these markers may have poor positive predictive values for the detection of subclinical, histologic chorioamnionitis and may be variably expressed within the amniotic fluid and fetal membranes during chorioamnionitis (22)(23)(24). Recently, Liu et al (25) reported that surface-enhanced laser desorption ionization-time of flight mass spectrometry (SELDI-TOF-MS) for the detection of human neutrophil defensin 1 (HNP-1) and HNP-2 and calgranulins A and C within amniotic fluid was highly accurate for the diagnosis of subclinical chorioamnionitis, but further studies with larger patient cohorts are required to validate these findings.…”
Section: Diagnosis Of Chorioamnionitismentioning
confidence: 99%
“…[11][12][13][14][15] Systemic maternal inflammation results in clinical chorioamnionitis, which refers to the presence of maternal fever associated with clinical signs (ie, foul-smelling discharge, uterine tenderness, and maternal and fetal tachycardia) as well as laboratory abnormalities such as leukocytosis. 16,17 In humans, intra-amniotic infection is associated with a local inflammatory response, 18 which is characterized by an increased amniotic fluid white blood cell (WBC) count [19][20][21][22][23] and elevated concentrations of inflammatory mediators, such as cytokines 18,24 and lipids (eg, prostaglandins). [25][26][27][28][29][30][31][32][33][34][35][36][37][38] In nonhuman primates, intra-amniotic infection also results in a local inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a paucity of studies done in the context of preterm gestation. Recent evidence derived from studies on clinical chorioamnionitis at term, as well as some early studies in preterm labor with intact membranes, suggests that a fraction of patients with this diagnosis have neither intra-amniotic infection nor intra-amniotic inflammation [45, 46]. In other words, some patients with preterm clinical chorioamnionitis appear to have a false-positive diagnosis.…”
Section: Introductionmentioning
confidence: 99%